AKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH DEPOSITO MUDHARABAH BANK SYARIAH DI INDONESIA (Periode Tahun 2013-2016) - Rosi Astrika Agustina; Dina Fitrisia Septiarini (Universitas Airlangga, 2018)
The aim of the study was to determine influence inflation, profit sharing level and corporation size to mudharabah deposit amount of Islamic banks in Indonesia year of period 2013-2016. This study used quantitative approach. The data used for this study are quarterly data gathered from per quarterly financial report of Islamic banks in Indonesia period 2013- 2016. Dependent variable in the study is profit sharing level and corporation size, then independent variable are inflation. This research used analisys technical panel data regression. The regression result of this study indicate that variable that the inflation and the size of the company a significant effect on the mudharabah deposit amount. While, variable that the variable level revenue sharing significant effect on the amount of mudharabah deposit Islamic bank in Indonesia REFERENCESAl-Qur’an dan Terjemahannya.Agustiano, 2005. Penentuan Bagi Hasil Deposito Mudharabah di Bank Syariah, Dalam www.iaei-pusat.net.Ajija,Shochrul R dkk.2011. Cara Cerdas Menguasai Eviews.Jakarta: Salemba Empat.Andriyanti, Ani dan Wasilah. 2010. Faktor-faktor yang Mempengaruhi Jumlah Penghimpunan Dana Pihak Ketiga (Deposito Mudharabah 1 Bulan) Bank Muamalat Indonesia (BMI). Jurnal Simposium Nasional Akuntansi XIII Purwokerto, Universitas Jenderal Soedirman Purwokerto.Antonio,Muhammad Syafi’i.2001.Bank Syariah Dari Teori Ke Praktek.Jakarta : Gema Insani Pers.———————————–. 2009. Bank Syariah Dari Teori Ke Praktik. Jakarta : Gema Insani Pers.Ascarya. 2006. Akad dan Produk Bank Syariah. Jakarta : Raja Grafindo.———–.2007. Akad dan Produk Bank Syariah.Jakarta : Raja Grafindo.Badan Pusat Statistik, Statistik Inflasi Indonesia Tahun 2010 – 2016.Bank Indonesia, Outlook Perbankan Syariah 2015———–. Statistik Perbankan Syariah 2016Bungin, Burhan. 2005..Metode Penelitian Kuantitatif.Jakarta : Kencana.Eugene F. Brigham dan Joel F. Houston. 2010. Dasar – Dasar Manajemen Keuangan.Jakarta : Salemba Empat.Haron, Sudin dan Norafifah Ahmad. 2000. The Effects of Conventional Interest Rates and Rate of Profit on Funds Deposited with Islamic Banking System in Malaysia. Jurnal Internasional Journal of Islamic Financial Services Vol.1 104.Husni, Azhari. 2009. Faktor-faktor yang Mmepengaruhi Penghimpunan Dana Pihak Ketiga pada Perbankan Syariah di Indonesia periode : Januari 2006 – Desember 2007.Huda,N.,Idris., Nasution,M.E., Wiliasih, R. 2009. Eekonomi Makro Islam : Pendekatan Teoritis. Edisi 1. Jakarta : Kencana Prenada Group.Indrianto,H dan B.Supomo.2002. Metodologi Penelitian Bisnis.Yogyakarta : BPFE UGM.Karim, Adiwarman. 2004. Bank Islam Analisis Fiqih dan Keuangan. Jakarta : PT. Grafindo Persada————————–.2007. Ekonomi Makro Islam. Jakarta : PT. Grafindo Persada.Kasmir.2013. Analisis Laporan Keuangan. Jakarta : Rajawali Pers.Menkiw. Georgy.2005. Pengantar Teori Makro. Jakarta : Erlangga.Nachrowi, Djalal Nachrowi, Hardius Usman. 2006. Pendekatan Populer dan Praktis Ekonometrika untuk Analisis Ekonomi dan Keuangan. Jakarta: Lembaga Penerbit Universitas Indonesia.Nur Anisa, Ahmad dan Lailatul. 2013. Faktor – Faktor Yang Mempengaruhi Pertumbuhan Deposito Mudharabah Bank Syariah. Jurnal Ilmu dan Riset Akuntansi. Sekolah Tinggi Ilmu Ekonomi Indonesia (STESIA). Surabaya.Rivai, Veithzal.dkk. 2007. Bank and Financial Institution Management Conventional And Sharia System. 1st edition,. Jakarta : PT Raja Grafindo Persada.Sudarsono, Heri. 2007. Bank dan Lembaga Keuangan Syariah (deskripsi dan ilustrasi). Yogyakarta : Ekonisia.Sugiyono. 2009. Metode Penelitian Bisnis. Bandung : Alfabeta.Yaya, Rizal, dkk.2009. Akuntansi Perbankan Syariah. Jakarta : Salemba Empat.http://www.bi.go.id http://www.ojk.go.id